The Technology of Organizing Binary Classes In "Russian Language and Culture of Speech" And "Foreign Language" As A Mechanism for Preparing Students for Professional Skills Competitions According to Worlds kills Standards - Lyudmila N. DEGTERENKO; Elena A. KONYAEVA; Natalya Yu. KORNEEVA; Mikhail V. KOZHEVNIKOV; Irina V. LAPCHINSKAYA; Svetlana G. LITKE; Larisa N. PAVLOVA; Irina G. SAMSONOVA (Communications of International Proceedings, 2021)
In order to prepare students for professional skills competitions according to WorldSkills standards, it becomes necessary to develop communication skills among students of educational organizations. In this regard, there is a need for a transition to innovative formats and learning technologies. The authors note that one of such formats is integrated learning, and pedagogical technologies that implement this format are the technology of binary classes, which is described in this article. The practical experience of conducting binary classes in the disciplines "Russian language and culture of speech" and "Foreign language" is given. The strengths of the presented technology are noted. In conclusion, it is concluded that the synthesis of a competency-based approach in the implementation of the Federal State Standard of Secondary Vocational Education in the disciplines "Russian Language and Speech Culture" and "Foreign Language" and the requirements of demonstration exams according to WorldSkills standards allows the implementation of the technology of binary learning.
Keywords: Secondary Vocational Education; Federal State Educational Standards; Integrated Learning; Binary Classes; Students' Communication Skills.